Present status of Dark green bulrush [Scirpus atrovirens (Wild.)] cultivation at Tala Upazila of Satkhira District (International Journal of Agricultural Research, Innovation and Technology, 2026)
Dark green bulrush [Scirpus atrovirens (Willd.)] cultivation has become a potential driver of socioeconomic growth in Tala Upazila of Satkhira District, Bangladesh during October to December, 2024. This study explores the current cultivation practices adopted by local farmers. A total of 41 respondents were selected using snowball sampling, and a descriptive and diagnostic research design was followed to analyze the data. The majority utilize traditional methods suited to wetland ecosystems, with 65.9% of them relying on a combination of irrigation and natural rainfall . Most growers are marginal farmers operating on small landholdings, with an average investment of approximately BDT 50,000 per hectare. Despite limited resources, all surveyed farmers reported that cultivation of Dark green bulrush is profitable. On average, they obtain over 700 bundles per hectare, each fetching around BDT 150 in local markets.  The study also reveals that a considerable number of cultivators have undergone training programs and possess substantial knowledge regarding crop management. Their primary motivation for cultivating this crop is income generation. The findings suggest a growing interest and positive outlook among farmers in this crop, driven by its economic benefits. Promoting Dark green bulrush cultivation under current practices is contributing meaningfully to the livelihood improvement of small-scale farmers in this coastal region. The study highlights its emerging role in strengthening rural income and supporting economic resilience. Continued encouragement of such initiatives may play an important role in promoting locally adapted and income-generating agricultural practices across the region.Int. J. Agril. Res. Innov. Tech. 15(2): 39-56, Dec 2025